DYNAMICAL FACTORS AFFECTING OZONE MIXING RATIOS IN THE ANTARCTIC LOWER STRATOSPHERE - シオタニ, マサト; /; SHIOTANI, Masato; GILLE, John C.; LYJAK, Lawrence V. (1987)
P(論文) This study shows the climatology and interannual variability of dynamical quantities and ozone mixing ratios during the southern hemisphere spring. Analyses are made mainly for six years, from 1979 to 1984,September through December, using the temperature and geopotential height data provided by the National Meteorological Center (NMC) and the ozone mixing ratio data derived from the solar backscatter ultraviolet (SBUV) instrument on board the Nimbus 7. The zonal mean climatology shows that the coldest temperatures and zonal winds move poleward and downward from September through November, probably in response to wave forcing. A steep decrease in zonal mean ozone mixing ratios is observed around 60°S toward the south pole in September. With time, this high latitude ozone minimum (or "ozone hole") gets shallower in association with minor warmings and a final warming. Climatological synoptic charts in the lower stratosphere show the circumpolar circulation in the geopotential height field and a prominent planetary wave 1 in the temperature and ozone fields. The phases of the temperature and ozone waves in the lower stratosphere are very similar. The year-to-year variation of the ozone mixing ratio at high latitudes is related to that of the wave activity during the winter and spring. When the wave activity is vigorous, there are weaker westerlies, higher temperatures and higher ozone mixing ratios at high latitudes. It is possible that the long term change in the lower stratosphere are also related to the long-term trend in wave activity, although the evidence is not clear. Because the wave activity in 1979 was very vigorous, a simple comparison of atmospheric states between the 1979 and other recent years could lead to misleading conclusions on the rate of ozone decrease over the Antarctic. A long-term chemical effect is not precluded. departmental bulletin paper